Evaluation of seasonality in the diagnosis of acute myeloid leukaemia among adults in the United States, 1992–2008. (28th November 2012) - Calip, Gregory S.; McDougall, Jean A.; Wheldon, Mark C.; Li, Christopher I.; De, Anneclaire J.
P